2014
DOI: 10.1188/14.onf.e326-e342
|View full text |Cite
|
Sign up to set email alerts
|

Are Exercise Programs Effective for Improving Health-Related Quality of Life Among Cancer Survivors? A Systematic Review and Meta-Analysis

Abstract: Purpose/Objectives To evaluate the effectiveness of exercise interventions on overall health-related quality of life (HRQOL) and its domains among cancer survivors who have completed primary treatment. Data Sources 11 electronic databases were searched from inception (dates varied) to October 2011. The authors also identified eligible trials through a search of additional sources. Data Synthesis 40 trials with 3,694 participants met the inclusion criteria. At 12 weeks, cancer survivors exposed to exercise … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
90
1
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(99 citation statements)
references
References 62 publications
2
90
1
6
Order By: Relevance
“…A possible reason for that is the contribution of social interactions involving group exercising as well as the effect of distracting attention from the disease and treatment, which helps to reduce the negative impact (21). Mishra et al found in their meta-analysis the positive effects of exercise on health-related quality of life in different domains of functioning in cancer patients after the treatment was completed (22). This points to the importance of systematically involving different physical activity programs in clinical guidelines or recommendations for work in phases of rehabilitation and inclusion of a physiotherapist as a mandatory member of a multidisciplinary team.…”
Section: Discussionmentioning
confidence: 99%
“…A possible reason for that is the contribution of social interactions involving group exercising as well as the effect of distracting attention from the disease and treatment, which helps to reduce the negative impact (21). Mishra et al found in their meta-analysis the positive effects of exercise on health-related quality of life in different domains of functioning in cancer patients after the treatment was completed (22). This points to the importance of systematically involving different physical activity programs in clinical guidelines or recommendations for work in phases of rehabilitation and inclusion of a physiotherapist as a mandatory member of a multidisciplinary team.…”
Section: Discussionmentioning
confidence: 99%
“…Of those interventions, physical activity and psychoeducation seem promising with respect to fatigue, anxiety, depression, stress, physical functioning, and qol in bca patients and survivors 42,54,61,63 . The findings concerning physical activity are in line with a recent report published by Segal …”
Section: Discussionmentioning
confidence: 99%
“…Evidence from randomized controlled trials documents the ability of rigorously designed and implemented exercise interventions to ameliorate many adverse effects of cancer treatments, including reduced hrqol 6,8 . In an initial effort to move the available research into practice, community-based cancer-specific exercise programs, offered free of charge or for a nominal fee, have been developed through partnerships with universities or not-for-profit organizations.…”
Section: Introductionmentioning
confidence: 99%
“…Many of those side effects can be long-term and can affect health-related quality of life (hrqol) 6 , a concept that encompasses subjective perceptions of both physical and emotional symptoms and side effects of treatment 7 .…”
Section: Introductionmentioning
confidence: 99%